The EXPLORING THE AFFECTING RELATIONSHIP FACTOR OF JOB PERFORMANCE IN PT. PAMAPERSADA NUSANTARA - Wardana, Kurniawan Pitta; Sugiharto, Erfan; Yuansa, Futra Kurnia; Syamil, Ahmad (LPPM of NAROTAMA UNIVERSITY, 2023)
Purpose: This research proposes to examine the relationship between job performance and empathic leadership, job satisfaction, and work engagement. Design/methodology/approach: The quantitative research technique is referred to as the research method. The target of this research is PT. Pamapersada Nusantara, and the research sample, which consists of 386 respondents, refers to the structural equational modelling model. Findings: The findings demonstrated that the respondents believed that each and every hypothesis had been confirmed. Research limitations/implications: The study only focused on a specific set of factors that may influence job performance, such as individual crafting, supervisory support, and work engagement. Other factors, such as organisational culture or job demands, were not explored in depth. It is important for future research to investigate these additional factors and their potential impact on job performance at PT. Pamapersada Nusantara. Despite these limitations, this study contributes to the understanding of the factors that influence job performance in the mining industry and provides insights for practitioners to develop effective interventions to enhance job performance among employees. Practical implications: The managerial implication of this research is that the company can enhance job satisfaction and work engagement, boost employee performance, achieve their objectives, and acquire a competitive edge. To ensure they meet organisational goals and improve safety, technical and non-technical training programmes must be evaluated. This assessment should assess teacher preparedness, classroom, simulator, and field practise efficacy, training material content, and employee benefits. Companies may boost employee engagement, performance, and safety by strengthening training programmes and meeting employee requirements. Originality/value: This report originates from research conducted inside a single mining business. Paper type: Research Paper.